Vasodilation increases pulse pressure variation, mimicking hypovolemic status in rabbits (Clinics, 2010)
OBJECTIVE: To test the hypothesis that pulse pressure respiratory variation (PPV) amplification, observed in hypovolemia, can also be observed during sodium nitroprusside (SNP)-induced vasodilation. INTRODUCTION: PPV is largely used for early identification of cardiac responsiveness, especially when hypovolemia is suspected. PPV results from respiratory variation in transpulmonary blood flow and reflects the left ventricular preload variations during respiratory cycles. Any factor that decreases left ventricular preload can be associated with PPV amplification, as seen in hypovolemia. METHODS: Ten anesthetized and mechanically ventilated rabbits underwent progressive hypotension by either controlled hemorrhage (Group 1) or intravenous SNP infusion (Group 2). Animals in Group 1 (n = 5) had graded hemorrhage induced at 10% steps until 50% of the total volume was bled. Mean arterial pressure (MAP) steps were registered and assumed as pressure targets to be reached in Group 2. Group 2 (n = 5) was subjected to a progressive SNP infusion to reach similar pressure targets as those defined in Group 1. Heart rate (HR), systolic pressure variation (SPV) and PPV were measured at each MAP step, and the values were compared between the groups. RESULTS: SPV and PPV were similar between the experimental models in all steps (p >; 0.16). SPV increased earlier in Group 2. CONCLUSION: Both pharmacologic vasodilation and graded hemorrhage induced PPV amplification similar to that observed in hypovolemia, reinforcing the idea that amplified arterial pressure variation does not necessarily represent hypovolemic status but rather potential cardiovascular responsiveness to fluid infusion.